Sārānukrom klum chātphan Lāhū - Sōrot Sirisai (Sathāban Wičhai Phāsā læ Watthanatham ph̄ưa Patthanā chonnabot, Mahāwitthayālai Mahidon, 1996)
Commemorative volume brought out at 50th anniversary of enthronement of Bhumibol Adulyadej, King of Thailand, b. 1927.